Implementasi Model Discovery Learning Terhadap Peningkatan Hasil Belajar Menendang Bola Dengan Kaki Bagian Dalam - Irsan Kahar; Nur Wahidin Hakim; Arif Surullah (Ilmu Olahraga, 2023)
This study aims to improve the learning outcomes of kicking the ball using the inside of the foot in a soccer game using the discovery learning. This research is classroom action research (CAR). Data collection consists of four stages, namely planning, action implementation, observation and reflection. The number of samples was 15 people, namely class Va MIN 4. Data collection techniques were carried out by direct field tests starting from skills, attitudes, and knowledge. From the first cycle interval data, students who scored less than KKM 70 resulted in 12 students completing, 3 students not completing. From the description of learning outcomes, students get 80% completeness. The second cycle the researchers managed to improve by implementing the discovery learning of soccer material using the inner foot of the learning outcomes by motivating students according to the student's condition at that time, the result was 15 students in the complete category and 0 students incomplete or the percentage being 100%. Based on the data for each cycle and the discussion of the research results, it can be concluded that the application of the discovery to physical education subjects with the material of kicking a ball using the inside of the foot in soccer games can improve student learning outcomes. This is indicated by the increase in the results of research that has been carried out from cycle I and cycle II, namely 100%. by applying the learning model of discovery learning.